Density and temperature diagnostics of solar emission lines from NeV/MgV and SiVII/MgVII ions - Mohan A.; Dwivedi B.N.; Raju P.K. (My University, 2025)
We present NeV/MgV and SiVII/MgVII theoretical line intensity ratios as a function of electron density Ne and temperature Te. These are shown in the form of ratio-ratio diagrams, which should in principle allow both Ne and Te to be deduced for the emitting region of the solar plasma. We apply these diagnostics in the solar atmosphere, and discuss the available observations made from space. In most cases, however, we deduce Ne and Te from the computed absolute line intensities in a spherically symmetric model atmosphere of the Sun. Possible future applications of this investigation to spectral data from the Coronal Diagnostic Spectrometer (CDS) on the Solar and Heliospheric Observatory (SOHO) are briefly discussed.